DANDELION MISCHIEF - Aziz, Farida (Journal of Ayub Medical College Abbottabad, 1996)
Crying in an infant or young child can be an expression of many things, 1,2 e.g. 1. Hunger 2. Anger 3. Sadness 4. Discomfort 5. Pain, etc. In these, outside factors can be as much a contributory cause as from inside the body, e.g.: 1. An angry nappy rash getting sore and painful with a wet nappy. 2. An open pin somewhere in the clothes. 3. Any other foreign body 3 pressing somewhere on the body or inside, e.g. in the nose, ears, throat, etc.